(untitled) (Agora for Physical Education and Sport, 2024)
This paper evaluates how six special schools in Castilla-La Mancha (Spain) adapt Healthy School Projects (HSP), a program that promotes physical activity and healthy habits. The design of the HSP is both a facilitator and a barrier. Other facilitators include the involvement of the centers, collaboration with external agents, and the ability to adapt the program. Barriers include lack of training, place of residence, and COVID-19. Good practices are identified, and it is concluded that the programs are successful but need more support, coordination, and guidance.